Ocular rhinosporidiosis at a tertiary care center in West Bengal - Debasmita Nandi; Debolina Banerjee; Minerva Mandal; Maya Dutta; Swarupananda Biswas (Journal of Clinical Ophthalmology and Research)
Rhinosporidiosis is a chronic granulomatous disease presenting as a reddish polypoid pedunculated or friable mass caused by a parasitic protist; Rhinosporidium seeberi. It is hyperendemic in Sri Lanka and Southern India, with the hot tropical weather favoring the infection. The present series is of three rare cases of ocular rhinosporidiosis from West Bengal. All of them underwent total excision with electrocautery of the base and histopathological confirmation. None had any complication or recurrence on a follow-up of 1 year. Even though oculosporidiosis is comparatively rare, it should be considered as a possible differential in all conjunctival lesions and confirmed by histopathological examination.